Parents' perception and willingness to maintain provider care continuity for their children under universal health coverage - Yu Chen Tseng; I Jen Wang; Christy Pu (AIMS Press, 2019)
Background: Provider continuity of care (COC) is closely related to patient outcome in pediatrics. However, no study has investigated how parents perceive the importance of COC and whether their perceptions affect their willingness to make effort to maintain good provider COC for their children under universal health coverage. Methods: A cross-sectional survey was conducted between August 2017 and February 2018 across 6 different practices: 2 medical centers, 2 regional hospitals, 1 district hospital, and 1 clinic (n = 825). Parents' and caregivers' perceptions and perceived value of COC were evaluated using 7 items. The contingent valuation method was used to estimate willingness to pay and spend time. Results: Of all respondents, only 47% (n = 394) were willing to spend >30 minutes to have their children see the regular physician if the regular physician relocated. Approximately 38% (n = 302) respondents were willing to pay more than New Taiwan Dollar (NT$) 300 per month to maintain provider COC. The perception that high COC is important was associated with willingness to spend more time for maintaining high provider COC. Conclusion: Parents' perception of COC does not affect their willingness to pay for maintaining high provider COC for their children but affects their willingness to spend more time to maintain COC.